Study guides

☆☆

Q: 4n plus 6 equals

Write your answer...

Submit

Still have questions?

Related questions

12+4n = 2n12+4n-4n = 2n-4n12 = -2n-1/2(12 = -2n)-6 = n

If 7m = 4n+2 and 7m+2 = 8 m = 6/7 and n = 1

3n + 4n = 42 7n = 42 n = 42/7 n = 6

4n + 24 = 484n + 24 - 24 = 48 - 244n + 24 - 24 = 48 - 244n = 48 - 244n = 244n/4 = 24/44n/4 = 24/4n = 24/4n = 6

(4n + 1)*(2n + 6) = 8n2 + 26n + 6

It is an expression that can be simplified to -4n-1

2n+4n-12 = 06n-12+12 = 126n = 121/6(6n = 12)n = 2

n=6

8 = 4n n = 2

10n+12 = 14n-12 10n-14 = -12-12 -4n = -24 n = 6

(4n + 3)(n + 6) so n is either -3/4 or -6

No.

People also asked